Modern Religious Counseling Model in The Ancient Manuscript of Lontara Attorioloang Ri Wajo - Hesty Nur Rahmi; Patmawati Patmawati; Labi Hadji Sarip Riwarung (Graduate Program of Pontianak Institute of Islamic Studies, 2020)
Lontara Attorioloang ri Wajo is one of the ancient manuscripts of Bugis found in Sambas, ​​West Kalimantan. Although ancient manuscripts have long been recognized as being important sources of physical and spiritual life for indigenous peoples, they have not been properly researched in academic discourse. The study of ancient manuscripts is still rarely done by historical researchers in West Kalimantan. In fact, the texts cover many issues including important aspects of human life such as religion, nation, and other human needs. This study focuses on the counselors, themes, and model of religious counseling presented in the manuscript Lontara Attorioloang ri Wajo. Content analysis is employed to discuss the text with regard to counseling figures, themes of religious counseling, and counseling model. The data indicates that the Arung Matoae (king) in Wajo Kingdom was an important counselor in the region. He practiced religious counseling that covered monotheism, leadership, human relations, and relationships to the universe. The King applied individual and group counseling for his religious counseling activities. This study offers new insight into religious counseling science as it has been practiced by people in the past as recorded in the manuscript. Past cultural track records can be restored with in-depth studies of the text which may lead to multi-disciplines that involve counseling experts, philologists, and historians collaborating to reveal further research findings.